Implementasi Kebijakan Peraturan Bupati Bandung No 42 Tahun 2017 Tentang Retribusi Parkir Di Tepi Jalan Umum Kabupaten Bandung - Fathurohman, Denizar; MPA, TATI (Jurnal Identitas, 2023)
This study aims to find out how the Policy Implementation of Bandung Regent Regulation No. 42 of 2017 Concerning Parking Fees on Public Roadsides in Bandung Regency. The indicators used to analyze the Policy Implementation of Bandung Regent Regulation No. 42 of 2017 Concerning Parking Fees on Public Roadsides in Bandung Regency include Communication, Resources, Disposition and Bureaucratic Structure. This research is located in the Bandung Regency area. Then the research design used in this research is descriptive with a qualitative approach. Sources of data used are primary data and secondary data. Data collection techniques used were observation, interviews, collecting document data, collecting data from audio and visual materials. The data analysis technique used is information gathering, data reduction, data presentation, drawing conclusions. The results of this study indicate that policy implementers, especially the Department of Transportation, Regional Technical Implementation Units and parking attendants, have carried out policy implementation quite well, although in practice there are still many things that need to be improved and there must be more attitude from implementers to conduct outreach about parking rules and mechanisms. However, it can be seen from the variables of policy implementation related to communication, resources, disposition and bureaucratic structure that have been implemented by policy implementers. Keywords: Policy Implementation, Parking Retribution, Public Roadside